2006
DOI: 10.1103/physrevb.73.054434
|View full text |Cite
|
Sign up to set email alerts
|

Observation of oscillatory magnetoresistance periodic in1BandBinCa3Ru

Abstract: We report magnetoresistance oscillations in high magnetic fields, B, up to 45 T and over a wide range of temperature in the Mott-like system Ca 3 Ru 2 O 7 . For B rotating within the ac-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This is particularly evident in the magnetization data for the x 0:20 and Bjja axis (M a ), which clearly show that Cr substitution lowers T MI and rapidly raises T N , greatly extending the AFM-M state from an 8 K interval to one over 70 K nearest-neighbor spins. This is similar to SrRu 1ÿx Cr x O 3 and CaRu 1ÿx Cr x O 3 where the FM state is either strongly enhanced [14 -16] or induced [17] by Cr doping, respectively.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…This is particularly evident in the magnetization data for the x 0:20 and Bjja axis (M a ), which clearly show that Cr substitution lowers T MI and rapidly raises T N , greatly extending the AFM-M state from an 8 K interval to one over 70 K nearest-neighbor spins. This is similar to SrRu 1ÿx Cr x O 3 and CaRu 1ÿx Cr x O 3 where the FM state is either strongly enhanced [14 -16] or induced [17] by Cr doping, respectively.…”
supporting
confidence: 58%
“…The AFM ground state consists of ferromagnetic (FM) bilayers stacked antiferromagnetically along the orthorhombic c axis. An external magnetic field B leads to novel magnetoresistive properties [4 -9] that are consequences of strong spin-orbit coupling, including Shubnikov-de Haas oscillations within a partially-gapped Mott state [7,8], and oscillatory magnetoresistance that is periodic in magnetic field B (not 1=B) [10]. In particular, colossal magnetoresistance (CMR), which is driven by ferromagnetism in all other known materials [4], is attained in Ca 3 Ru 2 O 7 by avoiding a FM state [4 -6], hinting at a novel mechanism based upon orbital ordering within a highly anisotropic, antiferromagnetic metallic (AFM-M) state [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…As discussed above, as a 4d transition metal species, Ru 4+ has more extensive electron density distribution and contributes stronger SOC effect than the 3d ions [33]. These effects together with the induced lattice contraction are responsible for the observed phenomena.…”
Section: E Phase Diagrammentioning
confidence: 85%
“…First, 4d and even 5d magnetic ions in oxides usually exhibit magnetic moment different from those strongly correlated 3d ones, which benefits to modulate the spin frustration. Second, the relatively strong SOC of 4d ions allows a possibility of enhancing FE polarization via the inverse DM interaction since the DM coefficients of those 4d oxides are generally big [33]. Third, it has been repeatedly identified that the p-d orbit hybridization can be an essential ingredient for generating electronic dipole polarization, which seems to be the origin for ferroelectricity in multiferroic CuFeO 2 etc [34].…”
Section: +mentioning
confidence: 99%
“…The pure compound is ionic with valence Sr 2 , Ru 4 , and O 2ÿ , which would suggest the substitution of Ru 4 with Mn 4 upon doping. Interestingly, in the related compounds SrRu 1ÿx Cr x O 3 [10] and CaRu 1ÿx Cr x O 3 [11], one might also expect the naive Ru 4 ! Cr 4 substitution.…”
mentioning
confidence: 99%